Evaluation of Sanitation Risk of Toxic Waste Contaminated Soils - Kouadio, Olivier; Koffi, Antoine; Kouadio, Maxime Romeo; Gnamba, Frank Maxime; Dongo, Kouassi; Ouffoue, Koffi Sebastien (European Scientific Journal, ESJ, 2025)
This work aim to understand the sanitation risk of toxic waste on tropical contaminated soils. The Ivorian Antipollution Center discovered 540 m3 of the toxic waste from Probo Koala boat in 21 August, 2006. These toxic waste have been seen in 13 zones of the Abidjan district : Akouédo, Abobo, Abobo Alépé road (DJIBI village), civile prison road (MACA), industrial zone of Koumassi, Port-Bouët - Vridi CAP Logistic (Rue Saint-Sylvestre)… This situation caused a socio-political crisis and generated the death of many people. In the aim to know the environmental impact and health risk assessment of toxics waste, of these contaminated soils in Abidjan district (Ivory Coast) the samples of these toxic waste have been sent to analyses in France. This analyse show that the principal compound of thes toxic waste are Polycyclics Aromatics Hydrocarbons (PAH), Volatile Aromatics Compound (VAC), Mercaptans and sulfurs molecules, Heavy metal, sulfur, Aliphatic Hydrocarbons, Linear hydrocarbons and Total Petroleum Hydrocarbons (TPH). As these compounds present carcinogenic, toxic, and mutagenic properties, some of them were classified as priority pollutants by the US-EPA (Keith and Telliard 1979). In environment, the toxic waste cause the contamination of sols, water, air around the world (US-EPA, 1999). In this work, we want to present to you the risk of toxics waste on the health of people and the environment in the district of Abidjan.